PENGARUH METODE LATIHAN DRILL TERHADAP KEMAMPUAN SHOOTING PESERTA EKSTRAKURIKULER FUTSAL MAN 1 KUNINGAN - Didin Junaedi; Hana Astria Nur (STKIP Subang, 2025)
PENGARUH METODE LATIHAN DRILL TERHADAP KEMAMPUAN SHOOTING PESERTA EKSTRAKURIKULER FUTSAL MAN 1 KUNINGAN . This study aims to determine the Influence of the Drill Training Method on the Shooting Ability of Participants in the Extracurricular Program at MAN 1 Kuningan. The research method used is an experiment with a one group pretest-posttest design. The subjects of the study consisted of 20 students from MAN 1 Kuningan who participated in a training program for 6 weeks with a frequency of 2 meetings per week. The data collection instrument used was a shooting test on goal, where the goal area was divided into 9 sections. The results showed a significant increase in the shooting accuracy of the players, where the average pretest score of 13.3 increased to 31.9 in the posttest. The results of the paired sample t-test obtained a significance value of 0.001 (<0.05), indicating a significant effect of the shooting drill training on the ability.